ANALISIS URAIAN TUGAS KEPALA URUSAN TATA USAHA SEKOLAH DI SLTA SE-KOTA PADANG - Wahyu Pratama; Rusdinal Rusdinal; Jasrial Jasrial; Lusi Susanti (STKIP Pesisir Selatan, 2026)
The performance of duties by school administrative heads plays a crucial role in supporting the effectiveness of administrative services. However, the execution of these duties in senior high schools (SMA) in Padang City has not been extensively studied empirically. This study aims to describe the performance of these duties across senior high schools in Padang City, focusing on the aspects of task clarity, working conditions, authority, and responsibility. A quantitative approach utilizing a descriptive method was employed. The study population comprised 114 school administrative heads, with a sample of 54 respondents selected via proportional random sampling. Data were collected using a rating-scale questionnaire and analyzed descriptively using the Respondent Achievement Level (TCR) metric. The results indicate that duty performance falls into the